The Construction Of Roadbeds on Permafrost and in Swamps from Reinforced Soils of Increased Strength - Anatoly N. Shuvaev; Anton P. Smirnov; Sergey V. Kartavy (Civil Engineering Journal, 2020)
The paper presents the history of the transport infrastructure of the West-Siberian oil and gas complex in the last century and ways to solve the problems of road construction in the twenty-first century. The development of the territory of Siberia and the North in the present period is constrained by the low rates of development of the transport structure. One of the reasons for this lag is the lack of regulatory documents to substantiate transport structures in the harsh climatic and difficult soil and geological conditions based on the use of new modern road-building materials. The development of new resource-saving materials, structures and technologies based on local building materials, products and industrial waste using modern methods and research methods in materials science is an aim of current study. The general research methodology consisted of theoretical, laboratory and field studies. The developed designs and technologies for the construction of embankments in permafrost and in swamps using geotechnical holders filled with unsuitable soils (thawed and frozen waterlogged peat and clay soils) can reduce the volume of work and the cost of construction by one and a half to two times while increasing the service life of structures. The experimental sites of embankments constructed between 1995 and 2009 in the wetlands of the Uvat Group of deposits in the Tyumen Region and in permafrost in the areas of Novy Urengoy have been observed for more than ten years. The artificial stone material tested in Murmansk and Surgut based on the strengthening of local soils with inorganic binders with polymer additives using modern technologies allows it to be used instead of imported stone materials and reinforced concrete slabs for the construction of structural layers of road pavements, reinforcing slopes, as well as in hydraulic structures. The new artificial stone material is characterized by high strength and durability in areas with a temperature gradient of the external environment of more than 100 (from +50 to -50 °C).